Efficient and controllable sodium ion battery hard carbon negative electrode chemical sodium pre-treatment method
By reacting with aryl-sodium organic solution for chemical pre-sodium treatment, the problem of irreversible sodium ion loss during the cycle of the hard carbon anode of sodium ion battery is solved, which significantly improves the balun efficiency and energy density of the battery, and is suitable for industrial production.
Patent Information
- Application Number
- CN202411241673.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-10
AI Technical Summary
During the cycle, the hard carbon anode of sodium ion batteries is irreversible sodium ions due to defects in the interface film and structural structure of the solid electrolyte, resulting in low efficiency in the first circle and affecting the energy density of the battery.
Chemically pre-sodium treatment was prepared by reacting aryl-sodium organic solution with hard carbon negative electrode. Drop-added, washed and vacuum-dried through inert atmosphere to prepare sodium hard carbon negative electrode, increase active sodium and compensate for sodium ion capture on the electrode surface, improve Electrode structure.
It significantly improves the first-circle Coulomb efficiency of the hard carbon negative electrode and the discharge specific capacity of the whole battery, improves the cycle stability and energy density of the battery, is simple and safe to operate, and is suitable for industrial production.
Smart Images

Figure CN119297209A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for chemical pre-sodiumization of a hard carbon negative electrode of a sodium ion battery. Background Art
[0002] Lithium-ion batteries have been widely developed and applied due to their many advantages such as high energy density and long cycle life. However, the shortage of lithium resources in the earth's crust has become the biggest obstacle to the large-scale application of lithium-ion batteries. In recent years, sodium-ion batteries have attracted widespread attention due to their low cost and similar electrochemical properties to lithium-ion batteries. The development of high-performance sodium-ion batteries has become a hot topic.
[0003] After nearly a decade of development, sodium-ion batteries have made great progress in electrode materials. The negative electrodes, including carbon-based materials, conversion materials, alloy materials and organic materials, have shown relatively excellent cycle performance and rate performance. Among them, hard carbon negative electrode materials have been commercialized due to their wide sources and excellent performance. After more than a decade of research on the sodium storage mechanism of hard carbon negative electrodes, it was found that the storage behavior of sodium in hard carbon mainly includes (1) absorption of surface, defects and functional groups; (2) micropore filling; (3) graphite layer intercalation. The formation of solid electrolyte interface film and the absorption of sodium by defects, pores and oxygen-containing functional groups on the hard carbon surface during the first charge and discharge process consume a large amount of active sodium ions, resulting in low first-cycle coulombic efficiency of hard carbon negative electrodes. In the half-cell, the sodium content is excessive and there is no need to worry about sodium consumption; in the full cell, the consumption of active sodium directly reduces the battery capacity, resulting in the energy density of sodium-ion batteries being lower than that of lithium-ion batteries. Reducing or compensating for the irreversible sodium loss in hard carbon is the key to directly improving the first-cycle coulombic efficiency. One strategy is to adjust the microstructure of hard carbon by adjusting the carbonization temperature and heating rate during the synthesis process, thereby increasing the degree of graphitization and reducing defect sites; another strategy is to use functional electrolytes (ether solvents and concentrated salts) and artificial solid electrolyte interface membrane modifications, which can alleviate the irreversible solvent reduction on the electrode surface. Although these methods have a positive effect on improving the first-cycle coulombic efficiency of hard carbon anodes, they are still not enough to meet the requirements of commercial applications. Although physical pre-sodium and electrochemical pre-sodium can effectively improve the first-cycle coulombic efficiency of hard carbon anodes, they have defects such as poor safety and complex operating processes, which are not conducive to large-scale research. Summary of the invention
[0004] The present invention proposes an efficient and controllable chemical pre-sodium method for a hard carbon negative electrode of a sodium ion battery, the purpose of which is to solve the problem of irreversible sodium loss during the cycle of the sodium ion battery, including the capture of sodium ions by the solid electrolyte interface membrane and the negative electrode structural defects, and to improve the first-cycle coulombic efficiency of the hard carbon negative electrode of the sodium ion battery, so as to improve the cycle stability of the sodium ion battery and increase the energy density of the whole battery.
[0005] The technical solution for implementing the present invention is as follows:
[0006] A method for chemical pre-sodiumization of a sodium ion battery hard carbon negative electrode comprises reacting the sodium ion battery hard carbon negative electrode with an aryl-sodium organic solution, washing and drying to obtain a sodiumized hard carbon negative electrode.
[0007] Preferably, the method for chemical pre-sodiumization of the sodium ion battery hard carbon negative electrode is: in an inert atmosphere, dripping an aryl-sodium organic solution onto the sodium ion battery hard carbon negative electrode plate, then washing and vacuum drying to obtain a sodiumized hard carbon negative electrode.
[0008] Preferably, the solvent of the aryl-sodium organic solution is one of ethylene glycol dimethyl ether or tetrahydrofuran.
[0009] Preferably, the solute of the aryl-sodium organic solution is 9-methylfluorene-sodium, 9,9-dimethylfluorene-sodium and its derivative-sodium, and the concentration of the solute is 0.001-2 mol L -1 The amount of the aryl-sodium organic solution added is 1 to 100 μL mg according to the mass of the hard carbon negative electrode active material. -1 .
[0010] Preferably, the aryl-sodium organic solution can be prepared by the following method: dissolving metallic sodium in an organic solvent of aryl-ethylene glycol dimethyl ether or aryl-tetrahydrofuran in a glove box filled with argon.
[0011] Preferably, after the reaction is complete, the mixture is washed with ethylene glycol dimethyl ether for three times and dried in vacuo at 80° C. to obtain a pre-sodiumized hard carbon negative electrode sheet.
[0012] Preferably, the hard carbon negative electrode plate should include the following components: 70-95% hard carbon negative electrode active material, 2.5-20% conductive agent, 2.5-10% binder. The conductive agent is one of SuperP, Ketjen black, and acetylene black. The binder includes one of sodium carboxymethyl cellulose, polyvinyl alcohol, sodium alginate, and polyvinylidene fluoride.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] The present invention uses an efficient aryl-sodium organic pre-sodium reagent to chemically pre-sodiumize the hard carbon negative electrode of the sodium ion battery. The method is simple to operate, safe to react, can accurately control the degree of pre-sodiumization of the hard carbon negative electrode, and is easy to scale up and realize industrial production. After the hard carbon negative electrode plate is pre-sodiumized, the sodiumized plate can provide additional active sodium to compensate for the irreversible sodium loss during the battery cycle, including the capture of sodium ions by the solid electrolyte interface membrane and the negative electrode structural defects. The first cycle coulomb efficiency of the hard carbon half-cell is significantly improved, and the discharge specific capacity of the full battery is significantly improved, which is beneficial to improve the energy density of the full battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a scanning electron microscope image of the hard carbon negative electrode sheet obtained in Example 1.
[0016] Figure 2 This is a scanning electron microscope image of the pre-sodium hard carbon negative electrode obtained in Example 1.
[0017] Figure 3 This is the first cycle charge and discharge curve of the pre-sodium hard carbon negative electrode half-cell obtained in Example 1.
[0018] Figure 4 This is the long cycle performance diagram of the pre-sodium hard carbon negative electrode half-cell obtained in Example 1.
[0019] Figure 5 This is the first cycle charge and discharge curve of the hard carbon negative electrode half-cell obtained in Example 1.
[0020] Figure 6 This is the first cycle charge and discharge curve of the pre-sodium hard carbon negative electrode half-cell obtained in Example 2.
[0021] Figure 7 This is the first cycle charge and discharge curve of the pre-sodium hard carbon negative electrode half-cell obtained in Example 3.
[0022] Figure 8 This is the first cycle charge and discharge curve of the full battery assembled with the hard carbon negative electrode sheet after pre-sodium treatment obtained in Example 4.
[0023] Fig. 9 This is the long cycle performance diagram of the full battery assembled with the hard carbon negative electrode plates after pre-sodium treatment obtained in Example 4.
[0024] Fig.10 This is the first cycle charge and discharge curve of the full battery assembled with the hard carbon negative electrode piece matched with the positive electrode obtained in Example 2.
[0025] Fig.11 This is the first cycle charge and discharge curve of the hard carbon negative electrode half-cell after pre-sodium obtained in Example 5.
[0026] Fig.12 This is the first cycle charge and discharge curve of the hard carbon negative electrode half-cell after pre-sodium treatment obtained in Example 6. DETAILED DESCRIPTION
[0027] The present invention provides an efficient and controllable method for chemical pre-sodiumization of a hard carbon negative electrode for a sodium ion battery. In the following embodiments, the hard carbon negative electrode for a sodium ion battery is reacted with an aryl-sodium organic solution, and then washed and dried to obtain a sodiumized hard carbon negative electrode. The reaction is carried out in an inert atmosphere, and the aryl-sodium organic solution is dripped onto a hard carbon negative electrode plate for a sodium ion battery, and then washed and vacuum dried to obtain a sodiumized hard carbon negative electrode. The solvent of the aryl-sodium organic solution is one of ethylene glycol dimethyl ether or tetrahydrofuran. In the following embodiments, the hard carbon negative electrode plate comprises the following components: 70-95% hard carbon negative electrode active material, 2.5-20% conductive agent, and 2.5-10% binder; the conductive agent is one of SuperP, Ketjen black, and acetylene black; the binder comprises one of sodium carboxymethyl cellulose, polyvinyl alcohol, sodium alginate, and polyvinylidene fluoride.
[0028] The present invention will be further explained below through the accompanying drawings and specific examples. The following examples are only used as an illustration and should not be understood as limiting the scope of the present invention. The protection scope of the present invention is not limited to the following embodiments.
[0029] Example 1
[0030] In an inert atmosphere, equimolar amounts of 9,9-dimethylfluorene and sodium were mixed and dissolved in ethylene glycol dimethyl ether solvent. After reaction at room temperature, a concentration of 0.2 mol L -1 9,9-dimethylfluorene-sodium ethylene glycol dimethyl ether solution. According to the mass of hard carbon negative electrode active material, the amount of chemical pre-sodium solution added is 20μLmg -1 After the reaction is complete, it is washed with ethylene glycol dimethyl ether for three times and dried in vacuum at 80°C to obtain a pre-sodiumized hard carbon negative electrode. The scanning electron microscope images of the hard carbon negative electrode before and after pre-sodiumization are shown in Figure 2. Figure 1 and Figure 2 As shown, the results indicate that pre-sodium treatment has no effect on the particle size of hard carbon.
[0031] The half-cell was assembled using the pre-sodiumized hard carbon anode and the constant current charge and discharge test was performed at room temperature using the Land CT2001A battery test system. The hard carbon half-cell test voltage range was 0.01-2V and the current density was 30mA g -1 ,like Figure 3 As shown in the figure, after the hard carbon negative electrode was pre-sodiumized, the open circuit voltage of the half-cell was 0.8 V, indicating that the pre-sodiumization of the hard carbon negative electrode was successfully achieved. The first cycle charge and discharge specific capacities of the pre-sodiumized hard carbon negative electrode half-cell were 290.7 and 290.4 mAh g -1 The first-cycle coulombic efficiency of the pre-sodiumized hard carbon negative electrode half-cell was significantly improved, reaching 100.10%. Figure 4 The half-cell with hard carbon anode after pre-sodiumization is charged at a current density of 300 mAg -1The long cycle performance diagram shows that the capacity retention rate after 200 cycles is 97.68% and the Coulomb efficiency is close to 100%, indicating that the chemical pre-sodium treatment has no effect on the cycle stability of the hard carbon material.
[0032] Comparative Example 1:
[0033] The half-cell was assembled using the hard carbon negative electrode sheet and the constant current charge and discharge test was performed at room temperature using the Land CT2001A battery test system. The hard carbon half-cell test voltage range was 0.01-2V and the current density was 30mA g -1 ,like Figure 5 As shown in the figure, the open circuit voltage of the hard carbon half-cell is 2.2 V, and the first cycle charge and discharge specific capacities are 289.9 and 330.7 mAh g -1 .
[0034] Example 2
[0035] In an inert atmosphere, equimolar amounts of 9,9-dimethylfluorene and sodium were mixed and dissolved in ethylene glycol dimethyl ether solvent. After reaction at room temperature, a concentration of 0.2 mol L -1 9,9-dimethylfluorene-sodium ethylene glycol dimethyl ether solution. According to the mass of hard carbon negative electrode active material, the amount of chemical pre-sodium solution added is 10μLmg -1 After the reaction was complete, the product was washed with ethylene glycol dimethyl ether for three times and dried under vacuum at 80°C to obtain a pre-sodiumized hard carbon negative electrode.
[0036] The half-cell was assembled using the pre-sodiumized hard carbon anode and the constant current charge and discharge test was performed at room temperature using the Land CT2001A battery test system. The hard carbon half-cell test voltage range was 0.01-2V and the current density was 30mA g -1 ,like Figure 6 As shown in the figure, after the hard carbon negative electrode was pre-sodiumized, the open circuit voltage of the half-cell was 1.1V, indicating that the pre-sodiumization of the hard carbon negative electrode was successfully achieved. The first cycle charge and discharge specific capacities of the pre-sodiumized hard carbon negative electrode half-cell were 293.2 and 303.6 mAh g -1 The first-cycle coulombic efficiency of the pre-sodiumized hard carbon negative electrode half-cell has been improved to 96.56%.
[0037] Example 3
[0038] In an inert atmosphere, equimolar amounts of 9,9-dimethylfluorene and sodium were mixed and dissolved in ethylene glycol dimethyl ether solvent. After reaction at room temperature, a concentration of 0.2 mol L -1 9,9-dimethylfluorene-sodium ethylene glycol dimethyl ether solution. According to the mass of hard carbon negative electrode active material, the amount of chemical pre-sodium solution added is 30μLmg -1After the reaction was complete, the product was washed with ethylene glycol dimethyl ether for three times and dried under vacuum at 80°C to obtain a pre-sodiumized hard carbon negative electrode.
[0039] The half-cell was assembled using the pre-sodiumized hard carbon anode and the constant current charge and discharge test was performed at room temperature using the Land CT2001A battery test system. The hard carbon half-cell test voltage range was 0.01-2V and the current density was 30mA g -1 ,like Figure 7 As shown in the figure, after the hard carbon negative electrode was pre-sodiumized, the open circuit voltage of the half-cell was 0.7 V, indicating that the pre-sodiumization of the hard carbon negative electrode was successfully achieved. The first cycle charge and discharge specific capacities of the pre-sodiumized hard carbon negative electrode half-cell were 291.8 and 278.8 mAh g -1 The first-cycle coulombic efficiency of the pre-sodiumized hard carbon negative electrode half-cell was greatly improved, reaching 104.68%.
[0040] Example 4
[0041] In an inert atmosphere, equimolar amounts of 9,9-dimethylfluorene and sodium were mixed and dissolved in ethylene glycol dimethyl ether solvent. After reaction at room temperature, a concentration of 0.2 mol L -1 9,9-dimethylfluorene-sodium ethylene glycol dimethyl ether solution. According to the mass of hard carbon negative electrode active material, the amount of chemical pre-sodium solution added is 20μLmg -1 After the reaction was complete, the product was washed with ethylene glycol dimethyl ether for three times and dried under vacuum at 80°C to obtain a pre-sodiumized hard carbon negative electrode.
[0042] The full battery was assembled using a pre-sodiumized hard carbon negative electrode and a sodium vanadium fluoride phosphate positive electrode. The constant current charge and discharge test was performed using a LandCT2001A battery test system at room temperature. The full battery test voltage range was 1.5-4.2V, and the current density was 10mAg -1 ,like Figure 8 As shown in the figure, the pre-sodiumized hard carbon anode is matched with the sodium vanadium fluoride phosphate cathode, and the open circuit voltage of the full battery is 2V, indicating that the pre-sodiumization of the hard carbon anode is successfully achieved. The first cycle charge and discharge specific capacities of the pre-sodiumized hard carbon anode and the sodium vanadium fluoride phosphate cathode half-cell are 123.9 and 108.5 mAh g -1 , the first-cycle Coulomb efficiency was increased to 87.57%. Fig. 9 The long cycle performance diagram of the full battery with a pre-sodiumized hard carbon negative electrode matched with a sodium vanadium fluorophosphate positive electrode shows that when the current density is 100 mA / g, the specific capacity of the full battery is significantly improved, and the cycle stability is excellent. The capacity retention rate after 200 cycles is 96.2%, and the coulombic efficiency is close to 100%, indicating that the pre-sodium treatment of the hard carbon negative electrode effectively improves the first-cycle coulombic efficiency and capacity utilization of the full battery.
[0043] Comparative Example 2:
[0044] The full battery was assembled using a hard carbon negative electrode and a sodium vanadium fluoride phosphate positive electrode. The constant current charge and discharge test was performed at room temperature using the Land CT2001A battery test system. The full battery test voltage range was 1.5-4.2V, and the current density was 10mAg -1 ,like Fig.10 As shown, the open circuit voltage of the full battery is 0 V, and the first cycle charge and discharge specific capacities are 116.3 and 90.1 mAh g -1 , the first-cycle coulombic efficiency is only 77.47%, indicating that the sodium ions in the full battery system are irreversibly consumed, resulting in low energy density of the full battery.
[0045] In summary, the use of 9,9-dimethylfluorene-sodium-ethylene glycol dimethyl ether reagent for chemical pre-sodium treatment of the hard carbon negative electrode of the sodium ion battery is simple to operate and has a safe reaction. It can accurately control the degree of sodiumization of the hard carbon negative electrode and significantly improve the discharge specific capacity of the whole battery, which is of great significance to the improvement of the energy density of the sodium ion battery soft pack battery.
[0046] In addition, the use of 9-methylfluorene-sodium organic pre-sodium reagent has the same technical effect as the above embodiment.
[0047] Embodiment 5:
[0048] In an inert atmosphere, equimolar amounts of 9,9-dimethylfluorene and sodium were mixed, dissolved in tetrahydrofuran solvent, and reacted at room temperature to obtain a concentration of 0.2 mol L -1 According to the mass of the hard carbon negative electrode active material, the amount of chemical pre-sodium solution added is 20μLmg -1 After the reaction was complete, the product was washed with tetrahydrofuran for three times and dried under vacuum at 80°C to obtain a pre-sodiumized hard carbon negative electrode.
[0049] At room temperature, constant current charge and discharge tests were performed using a Land CT2001A battery test system. The hard carbon half-cell test voltage range was 0.01-2V, and the current density was 30mAg -1 ,like Fig.11 As shown in the figure, after the hard carbon negative electrode was pre-sodiumized, the open circuit voltage of the half-cell was 0.8 V, indicating that the pre-sodiumization of the hard carbon negative electrode was successfully achieved. The first cycle charge and discharge specific capacities of the half-cell were 291.2 and 291.3 mAh g -1 The first-cycle coulombic efficiency of the pre-sodiumized hard carbon negative electrode half-cell was significantly improved, reaching 99.96%.
[0050] Embodiment 6:
[0051] In an inert atmosphere, 9-methylfluorene and sodium in equal molar amounts were mixed and dissolved in ethylene glycol dimethyl ether solvent. After reaction at room temperature, a concentration of 0.2 mol L -19-methylfluorene-sodium ethylene glycol dimethyl ether solution. According to the mass of hard carbon negative electrode active material, the amount of chemical pre-sodium solution added is 20μLmg -1 After the reaction was complete, the product was washed with ethylene glycol dimethyl ether for three times and dried under vacuum at 80°C to obtain a pre-sodiumized hard carbon negative electrode.
[0052] At room temperature, constant current charge and discharge tests were performed using a Land CT2001A battery test system. The hard carbon half-cell test voltage range was 0.01-2V, and the current density was 30mAg -1 ,like Fig.12 As shown in the figure, after the hard carbon negative electrode was pre-sodiumized, the open circuit voltage of the half-cell was 0.9 V, indicating that the pre-sodiumization of the hard carbon negative electrode was successfully achieved. The first cycle charge and discharge specific capacities of the half-cell were 292.7 and 297.2 mAh g -1 The first-cycle coulombic efficiency of the pre-sodiumized hard carbon negative electrode half-cell was significantly improved, reaching 98.47%.
[0053] The embodiments described above are only preferred examples of the present invention and are not intended to limit the present invention in any form. There are other variations and modifications without exceeding the technical solutions described in the claims.
Claims
1. An efficient and controllable method for chemical pre-sodiumization of a hard carbon negative electrode for a sodium ion battery, characterized in that: The sodium-ion battery hard carbon negative electrode is reacted with an aryl-sodium organic solution, and the sodium-containing hard carbon negative electrode is obtained after washing and drying.
2. The method for chemical pre-sodiumization of a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The reaction is carried out in an inert atmosphere, wherein an aryl-sodium organic solution is dripped onto a hard carbon negative electrode plate of a sodium ion battery, and then washed and vacuum dried to obtain a sodiumized hard carbon negative electrode.
3. The method for chemical pre-sodiumization of a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The solvent of the aryl-sodium organic solution is one of ethylene glycol dimethyl ether and tetrahydrofuran.
4. The method for chemical pre-sodiumization of a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The solute of the aryl-sodium organic solution is one of 9-methylfluorene-sodium, 9,9-dimethylfluorene-sodium and their derivatives-sodium.
5. The method for chemical pre-sodiumization of a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The concentration of the solute in the aryl-sodium organic solution is 0.001-2 mol L -1 The amount of the aryl-sodium organic solution added is 1 to 100 μL mg according to the mass of the hard carbon negative electrode active material. -1 .
6. The method for chemical pre-sodiumization of a hard carbon negative electrode for a sodium ion battery according to claim 1 or 2, characterized in that: The aryl-sodium organic solution can be prepared by the following method: dissolving metallic sodium in an organic solvent of aryl-ethylene glycol dimethyl ether or tetrahydrofuran in a glove box filled with argon.
7. The method for chemical pre-sodiumization of a hard carbon negative electrode for a sodium ion battery according to claim 1 or 2, characterized in that: After the reaction is complete, the product is washed with ethylene glycol dimethyl ether for three times and dried in a vacuum at 80° C. to obtain a pre-sodiumized hard carbon negative electrode.
8. The method for chemical pre-sodiumization of a hard carbon negative electrode for a sodium ion battery according to claim 1, characterized in that: The hard carbon negative electrode plate includes the following components: 70-95% hard carbon negative electrode active material, 2.5-20% conductive agent, 2.5-10% binder; the conductive agent is one of SuperP, Ketjen black, and acetylene black; the binder includes one of sodium carboxymethyl cellulose, polyvinyl alcohol, sodium alginate, and polyvinylidene fluoride.
Citation Information
Cited By
Preparation method of esterified modified starch derived hard carbon negative electrode material and application of esterified modified starch derived hard carbon negative electrode material in sodium-ion battery
CN119833530A
A preparation method of esterified modified starch-derived hard carbon anode material and its application in sodium-ion batteries
CN119833530B
Sodium supplementing method of sodium ion battery hard carbon negative electrode material
CN121215765A
Positive / negative electrode coupled pre-sodium-modified sodium ion battery and construction method thereof
CN121618065A
Sodium pre-supplementing hard carbon negative electrode material as well as preparation method and application thereof
CN122224808A